A Pedestrian Detection System With Weak Classifiers - Tetik, Yusuf Engin; Bolat, Bulent (IEEE, 2013)
In this paper, a pedestrian detection system which uses sliding window approach to detect pedestrians in still digital images is presented. The proposed pedestrian detection system combines weak classifiers in an Adaboost like novel way to create a strong classifier. Besides, rectangle ratios and discrete cosine transform coefficients are used as features with the well-known rectangle differences method.
Keywords: pedestrian detection system; sliding window approach; weak classifiers; adaboost; rectangle differences; rectangle ratios; Engineering; Telecommunications